A Review of Unsolicited Comments on the CAHPS 5.0 Health Plan Survey. (October 2021) - Fifolt, Matthew; Patel, Kunal; Rucks, Andrew; Ford, Eric W.
The CAHPS Health Plan Survey (CAHPS 5.0) collects invaluable information regarding consumer experiences with their health plans, and these data inform healthcare policies at both the state and federal levels. The purpose of this paper was to explore unsolicited comments provided on the CAHPS 5.0 survey of one state's Medicaid program. Secondary data analysis was conducted of unsolicited, written comments received from Medicaid recipients who completed the CAHPS 5.0 adult or child postal survey between 2016 and 2018. The majority of unsolicited comments were moderately or very negative in attitude (or tone) for adult and child surveys. Analysis of unsolicited comments yielded 3 themes: positive experiences with Medicaid, limitations of coverage, and direct requests for assistance. Providing space for Medicaid patients to share comments and receiving further guidance for content analysis would provide valuable context for interpreting overall survey results. Comments may also help Medicaid program administrators respond to the frequently complex and challenging experiences of navigating a continually evolving state health insurance program by the most vulnerable populations.